PENGARUH PENGELOLAAN KEUANGAN, SISTEM AKUNTANSI, DAN INTERNAL AUDIT TERHADAP KUALITAS LAPORAN KEUANGAN DAERAH - Aprilia, Misye Rahma; Kusumawardani, Anisa (Unitri Press, 2025)
This study aims to examine the effect of regional financial management, regional financial accounting system, and the role of internal audit on the quality of financial statements. Motivated by the alleged corruption case of the Mayor of Semarang, this study uses quantitative methods with primary data processed using SmartPLS 4. The object of research is BPKAD Central Java Province, considering that BPKAD Semarang City is being audited by BPK. The results showed that regional financial management, regional financial accounting systems, and the role of internal audit had a significant positive effect on the quality of financial statements. The evaluation of model fit (goodness of fit) shows satisfactory results, with high F square values, strong R square, and SRMR that are still within acceptable limits. These findings indicate the importance of implementing good financial governance and effective supervision in improving the quality of local government financial statements, as well as their relevance in the context of corruption prevention.